APLIKASI DOSIS PUPUK ORGANIK KASGOT TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI PAKCOY (Brassica rapa L.) - Dzikrul Muhammad Ilham; Serdani, Army Dita; Puspitorini, Palupi; Endrawati, Tri (grafting, 2024)
Organic fertilization involves natural materials derived from the remnants of organisms such as animal deposits, animal remains, or deceased plant matter. The primary focus of this research is to observe the impact of Kasgot organic fertilizer usage on the overall growth and harvest yield of Pakcoy mustard greens, as well as to discover the superior method of applying Kasgot organic fertilizer to optimize its effect on the growth and yield of Pakcoy mustard greens. The experimental design employed in this study is a randomized group method. Conducted in Tawangsari, a location within the Garum District, Blitar Regency, the findings of this research indicate that the application rate of Kasgot organic fertilizer significantly affects the growth and yield of Pakcoy mustard greens. The most effective dosage variant reached a leaf area of 50.3075 cm², a plant height of 18.175 cm, the optimal leaf count at 14.75, and an average fresh plant weight of 47.75 grams.